Protective Effects of Amauroderma rugosum on Doxorubicin-Induced Cardiotoxicity through Suppressing Oxidative Stress, Mitochondrial Dysfunction, Apoptosis, and Activating Akt/mTOR and Nrf2/HO-1 Signaling Pathways. (1st June 2022) - Li, Jingjing; Cheng, Yanfen; Li, Renkai; Wu, Xiaoping; Zheng, Chengwen; Shiu, Polly Ho-Ting; Chan, Jacqueline Cho-Ki; Rangsinth, Panthakarn; Liu, Conghui; Leung, Susan Wai-Sum; Lee, Simon Ming-Yuen; Zhang, Chen; et al.
Abstract : Clinical outcomes for doxorubicin (Dox) are limited by its cardiotoxicity but a combination of Dox and agents with cardioprotective activities is an effective strategy to improve its therapeutic outcome. Natural products provide abundant resources to search for novel cardioprotective agents. Ganoderma lucidum (GL) is the most well-known edible mushroom within the Ganodermataceae family. It is commonly used in traditional Chinese medicine or as a healthcare product. Amauroderma rugosum (AR) is another genus of mushroom from the Ganodermataceae family, but its pharmacological activity and medicinal value have rarely been reported. In the present study, the cardioprotective effects of the AR water extract against Dox-induced cardiotoxicity were studied in vitro and in vivo . Results showed that both the AR and GL extracts could potentiate the anticancer effect of Dox. The AR extract significantly decreased the oxidative stress, mitochondrial dysfunction, and apoptosis seen in Dox-treated H9c2 rat cardiomyocytes. However, knockdown of Nrf2 by siRNA abolished the protective effects of AR in these cells. In addition, Dox upregulated the expression of proapoptotic proteins and downregulated the Akt/mTOR and Nrf2/HO-1 signaling pathways, and these effects could be reversed by the AR extract. Consistently, the AR extract significantly prolonged survival time, reversed weight loss, and reduced cardiac dysfunction in Dox-treated mice. In addition, oxidative stress and apoptosis were suppressed, while Nrf2 and HO-1 expressions were elevated in the heart tissues of Dox-treated mice after treatment with the AR extract. However, the GL extract had less cardioprotective effect against Dox in both the cell and animal models. In conclusion, the AR water extract demonstrated a remarkable cardioprotective effect against Dox-induced cardiotoxicity. One of the possible mechanisms for this effect was the upregulation of the mTOR/Akt and Nrf2/HO-1-dependent pathways, which may reduce oxidative stress, mitochondrial dysfunction, and cardiomyocyte apoptosis. These findings suggested that AR may be beneficial for the heart, especially in patients receiving Dox-based chemotherapy.